Enfermedad fibroquística del páncreas. Informe de siete casos. - Rojo Concepción, Manuel; Valls Pérez, Orlando; Vantour, Hilda; Quintero, Isabel; Nery Marínez, Rita; Cabrera, Pastor; Barroso, Esperanza; Bernal, Benito (Revista Cubana de Pediatría, 2023)
Presenta los casos detectados en los dos últimos años.